The coercive power and democratic transition in the post-uprising Middle East and North Africa. Issue 6 (18th August 2021) - Hecan, Mehmet; Farhaoui, Fouad
ABSTRACT: Time has shown that attempts to transition to democracy in the Middle East and North Africa (MENA) following the Arab Uprisings were no minor feat. In their experiments with democratization, MENA countries faced a number of challenges that remain underexplored. Even though each county's path towards democratic transition is multifaceted and multicausal, in this article we set out to understand why attempts to transition to democracy have largely failed in post-uprising MENA with the unique exception of Tunisia. We do so by examining four post-uprising cases – Egypt, Tunisia, Libya, and Yemen – from a comparative perspective focusing on the coercive power of the state. Our findings suggest that in the presence of weak state institutions that lose their monopoly over coercive means that constrain non-state actors, democratization tends to fail. Yet, even if state mechanisms are strong, challenges to democratic transitions can still persist, especially if such states house politically motivated security institutions, such as influential militaries, that favour authoritarian rule. Within the larger picture, this work also provides further inferences about the relationship between structural aspects of the state and processes of democratization.